2000
DOI: 10.1091/mbc.11.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Unfolding of Mitotic Newt Chromosomes by Applied Force

Abstract: The force-extension behavior of individual mitotic newt chromosomes was studied, using micropipette surgery and manipulation, for elongations up to 80 times native length. After elongations up to five times, chromosomes return to their native length. In this regime chromosomes have linear elasticity, requiring ϳ1 nN of force to be stretched to two times native length. After more than five times stretching, chromosomes are permanently elongated, with force hysteresis during relaxation. If a chromosome is repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
146
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(164 citation statements)
references
References 20 publications
15
146
0
Order By: Relevance
“…Our experiments on newt and Xenopus mitotic chromosomes removed from cells and manipulated with micropipettes showed that mitotic newt chromosomes could be doubled in length by roughly 1 nN forces (Houchmandzadeh et al 1997, Poirier et al 2000, in good accord with Nicklas (1963). We also found stretching force to vary nearly linearly with extension for elongations up to four times the native length, allowing us to summarize the elastic response with a number, the Fforce constant_ or slope of the force-versus-elongation curve.…”
Section: Mitotic Chromosome Stretching Elasticitymentioning
confidence: 53%
See 4 more Smart Citations
“…Our experiments on newt and Xenopus mitotic chromosomes removed from cells and manipulated with micropipettes showed that mitotic newt chromosomes could be doubled in length by roughly 1 nN forces (Houchmandzadeh et al 1997, Poirier et al 2000, in good accord with Nicklas (1963). We also found stretching force to vary nearly linearly with extension for elongations up to four times the native length, allowing us to summarize the elastic response with a number, the Fforce constant_ or slope of the force-versus-elongation curve.…”
Section: Mitotic Chromosome Stretching Elasticitymentioning
confidence: 53%
“…Methods have been developed to isolate and to carry out stretching experiments on single prometaphase chromosomes, using glass micropipettes (Houchmandzadeh et al 1997, Poirier et al 2000, Pope et al 2006). The method is broadly similar to microneedle-based manipulation of meiotic metaphase chromosomes inside grasshopper spermatocytes (Nicklas 1963(Nicklas , 1983, as well as to classic studies of lampbrush chromosome mechanics (Callan 1954).…”
Section: Chromosome-stretching Experimentsmentioning
confidence: 99%
See 3 more Smart Citations